The Interaction of Focus, Givenness, and Prosody: A Study of Italian Clause Structure - Samek-Lodovici, Vieri (Oxford Studies in Theoretical Linguistics, 2015)
This book provides an in-depth investigation of contrastive focalization in Italian, showing that its syntactic expression is systematically affected by the syntactic expression of discourse-givenness. The proposed analysis disentangles the properties genuinely associated with contrastive focalization from those determined by the most productive operations affecting discourse given phrases at the right periphery, namely right dislocation and marginalization. On this basis, it shows that in the default case contrastive focalization occurs in situ and that instances of left-peripheral focalization only arise when focus obligatorily evacuates a larger right-dislocating phrase, giving rise to a distribution of leftward-moved foci that generalizes well beyond the cases examined in Rizzi (1997) and most literature since. In its final chapter, the book examines the syntax-prosody interface, showing how focalization in situ and other key properties follow from the prosodic constraints governing stress placement, thus reinterpreting and extending Zubizarreta's (1998) analysis of p-movement and the role of prosody in shaping syntax. Overall, this book offers an evidence-backed radical departure from current views of focalization based on a fixed focus projection at the left periphery of the clause. It also provides the most comprehensive study of Italian marginalization and right dislocation available to date.